Case Study : Hidayah Lestari Agro Trading / Mas Alia Izzaty Mohd Salleh - Mohd Salleh, Mas Alia Izzaty (2021)
Hidayah Lestari Agro Trading is a quite popular frozen shop in Machang, Kelantan because Hidayah Lestari Agro Trading is the only frozen shop there. People always buying frozen items there because of its trusted quality. In this case study, I had done some research andiscover for more information and knowledge regarding to frozen food in Machang Kelantanthrough call with Encik Sazli Faukulami. I had chosen a frozen shop Hidayah Lestari Agro Trading which is located not far from Bandar Machang. The reasons on why I chose the business store are due to business strategy, marketing strategy, operational strategy, and their financial achievements. He shared a lot of important strategies that been done on order to stabilize the operation of the frozen food shop through his website. Creating this company was not easy as expected. Mr. Sazli Faukulami has faced various obstacles such as financial problems, lack of staff, transportation problem and so on. Yet thanks to his efforts, he managed to promote his frozen food to the public. In addition, he has also honed his skills by participating in various seminars and has obtained a certificate of approval in business. I am very proud of Mr. Sazli Faukulami for his unwavering perseverance. Failure could not break his passion in business. Mr. Sazli Faukulami's journey in doing business made me aware of the importance of trying something. It is not impossible that something will happen if we try hard.